Generalised error analysis of FRFT‐OFDM over Nakagami‐m fading channel with arbitrary m. Issue 9 (15th June 2017) - Trivedi, Vinay Kumar; Kumari, Saraswati; Kumar, Preetam
Abstract : In this study, generalised expression of probability of error ( P e ) for binary phase shift keying (BPSK) and quadrature PSK (QPSK) modulated fractional Fourier transform (FRFT)‐based orthogonal frequency division multiplexing (OFDM) system has been derived over frequency selective Nakagami‐ m fading channel for any arbitrary Nakagami parameter m in the presence of carrier frequency offset (CFO). The symbol error rate (SER) performance of FRFT‐based OFDM system has been found to be better than fast FT‐based OFDM system at different values of FRFT angle α for BPSK and QPSK. For different values of CFO, the optimum α at which the error rate is minimum has been found and used for analysis and simulation. It has been observed that over Nakagami‐ m frequency selective channel, SER expression of BPSK and QPSK for FRFT‐OFDM system exactly follows the Monte Carlo simulation in MATLAB.